THE SIGNIFICANCE OF NEOCLASSICAL THEORIES IN ECONOMIC GROWTH - Dilshod Qurbanov (European Science Publishing, 2025)
This article analyzes the theoretical foundations of neoclassical growth theories, particularly the Solow–Swan and Ramsey–Cass–Koopmans models, and their significance for economic policy. The article examines the impact of capital accumulation, labor force growth, and technological progress on long-term economic growth from a neoclassical perspective. It also compares the limitations of neoclassical growth theories with endogenous growth models and provides general conclusions on neoclassical model parameters in the context of Uzbekistan.
Keywords: Economic growth, neoclassical theory, Solow model, capital accumulation, technological progress, economic policy, Ramsey–Cass–Koopmans model.